Effect of greening on pollutant dispersion and ventilation at urban street intersections. (October 2021) - Guo, Xin; Gao, Zhi; Buccolieri, Riccardo; Zhang, Mingjie; Shen, Jialei
Abstract: To improve ventilation efficiency and reduce pollution concentration in urban spaces, eco-strategies, including greening, have been suggested. However, there is still very little evidence to assert the benefits of such greening options, particularly at urban street intersections. Therefore, in this work, air flow and pollutant dispersion within urban-like three-way, four-way, and roundabouts intersections are investigated with three simple and five combined greening layouts. Three-dimensional computational fluid dynamics (CFD) analysis using the Reynolds-averaged Navier–Stokes model was conducted considering multiple wind directions. The ventilation efficiency was evaluated using the ventilation indices purging flow rate (PFR) and net escape velocity (NEV). The investigation of simple greening layouts shows that shrubs alone may enhance increase ventilation (i.e., increase PFR and NEV), and trees could increase the pollutant concentration at the pedestrian level. A comparison of greening layouts combining trees and shrubs shows that the presence of greening reduces ventilation and worsens the pollution condition at street intersections, except for shrubs located in the central zone within roundabouts. Specifically, NEV decreases by 16%–43% at four-way and three-way intersections owing to the presence of greening. Greening layouts with two rows of trees located 2.2 m away from buildings show overall significant negative effects on ventilation, particularly for wind directions ϕ = 0°, 45°, and 90°. The impact of shrubs and trees on ventilation at the roundabout is less significant, with NEV varying by 4%–11%. Highlights: Shrubs and trees with different greening layouts at urban street intersections were investigated. The porous media model was verified using experimental data to be applied in the study. The purging flow rate (PFR), net escape velocity (NEV), and normalized average concentration of CO were employed. Greening reduced the ventilation at street intersections, except for shrubs located in the central zone within roundabouts. Two-row trees away from buildings negatively affected ventilation, particularly in some wind directions.